KORELASI KADAR HbA1c DENGAN MIKROALBUMINURIA PADA PASIEN DIABETES MELITUS DI KLINIK DAN LABORATORIUM BUNDA MULIA LUMAJANG: CORRELATION OF HbA1C WITH MICROALBUMINURIA IN DIABETES MELLITUS AT BUNDA MULIA CLINIC AND LABORATORY LUMAJANG - Rini, Yenny Puspa; Taharani, Wiwin Duata; Ekawati, Evy Ratnasari; Sundari, Titik (Jurnal SainHealth, 2025)
Diabetes Mellitus (DM) is a disease caused by the failure of the pancreas to carry out its function, namely to produce insulin. Lack of insulin will cause increased levels of glucose in the blood or also known as hyperglycemia. HbA1c and Microalbuminuria are screening tests used to detect the early onset of diabetic nephropathy. The purpose of this study was to determine whether there was a correlation between HbA1c levels and microalbuminuria in diabetes mellitus patients at Bunda Mulia Lumajang Clinic and Laboratory. The research method was descriptive analytic. The subjects of this study were Diabetes Mellitus prolanis patients at Bunda Mulia Lumajang Clinic and Laboratory who were taken randomly as many as 50 patients.. The results of this study are that there is a unidirectional positive relationship with a strong correlation between HbA1c levels and microalbuminuria in diabetes mellitus patients, with a correlation value of 0.722. Based on the results, can be concluded that there was a strong and positive correlation between HbA1c and urine microalbumin in diabetes mellitus patients.